Makna Garam Dan Terang Dalam Matius 5:13-16 Bagi Pengikut Kristus - Nathanail Sitepu (HARVESTER: Jurnal Teologi dan Kepemimpinan Kristen, 2022)
Jesus' Sermon on the Mount about the Salt and Light of the world in the Gospel of Matthew 5:13-16 is a figurative expression, so it is not possible to interpret it through literal or literal understanding. In this article the author uses a descriptive method, namely literature review, collecting data and analyzing verses 13-16 through word cases and translations from Greek and various Bible translations. Based on this research, it can be concluded that the meaning of salt and light refers to the identity of followers of Jesus Christ which is attached wherever they go and wherever they are.AbstrakKhotbah Yesus di Bukit tentang Garam dan Terang dunia dalam Injil Matius 5:13-16 merupakan suatu ungkapan figuratif, sehingga untuk memaknainya tidak boleh melalui pemahaman secara hurufiah atau literal. Dalam artikel ini penulis menggunakan metode deskriptif yaitu kajian literatur, mengumpulkan data-data dan menganalisis ayat 13-16 melalui kasus kata dan terjemahan dari bahasa Yunani dan berbagai terjemahan Alkitab. Berdasarkan penelitian ini disimpulkan bahwa makna garam dan terang menunjuk kepada identitas pengikut Yesus Kristus yang melekat kemanapun mereka pergi dan dimanapun mereka berada.